Comparison of Income Tax and Tax Reliefs According to Income Tax Laws and Regulations for Individual Residents in Indonesia and Singapore - Suprajadi, Lusy; Tiopan, Demson; Sewu, Pan Lindawaty Suherman; Yuniawaty, Yenny (Technium Social Sciences Journal, 2024)
This study focuses on a comparative analysis of income tax laws and regulations and tax reliefs in Indonesia and Singapore, employing a normative legal approach. It reveals that Singapore’s tax reliefs, reflecting the government’s shared values, address diverse family needs, including elderly care, child development, health, and housing. Conversely, Indonesia provides tax reliefs through non-taxable income to support families. Despite Indonesia’s well-structured tax system, the government should address challenges, including inflation and external constraints, impacting public purchasing power and contributing to a high-cost economy.